Fabrication and Characterization of SiO2-Fe3O4 Using Co-Precipitation Method - Ema Susantika Perangin-angin (Talenta Publisher, 2023)
The fabrication of SiO2-Fe3O4 has been successfully carried out using the co-precipitation method. The main materials used are silicon dioxide (SiO2) and natural sand (Fe3O4). The calcination was conducted at 180â„ƒ for 2 hours. The morphology, crystal structure, and magnetic properties were characterized using X-ray diffraction (XRD), scanning electron microscopy (SEM), and vibrating sample magnetometer (VSM). The XRD pattern shows the effect of the material composition on the crystal structure of SiO2-Fe3O4. The grain size of SiO2-Fe3O4 crystals decreases with the increasing composition of silicon. Results of SEM-EDX show that the composition on morphology SiO2-Fe3O4 is a silicon composition. The VSM result shows that sample 3 (composition 7:3) yielded a coercivity value of 114.60 Oe, remanence of 38.62 emu/g, and magnetization saturation of 76.26 emu/g. The distribution of particle size is 70 nm.